2016
DOI: 10.7860/jcdr/2016/20961.8119
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Evidence-Based Practices on Postoperative Pain in Patients undergoing Gastrointestinal Surgery in Amiralmomenin Hospital in Zabol During 2014-2015

Abstract: This study suggests that a high percentage of patients experienced acute postoperative pain despite routine nursing care, while evidence-based nursing practices could significantly alleviate pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The PMP in this study is an evidence-based pain management (EBPM) programme that significantly decreased the pain intensity and side effects of the treatment (nausea and drowsiness). This is similar to the findings from other studies where EBPMs were implemented for post-operative pain management in different populations such as patients undergoing abdominal surgery (Joshi et al 2013), gastrointestinal surgery (Haghighi et al 2016), cardiac surgery (Rafiq et al 2014) and (Ard o et al 2018;Dinic et al 2018;Hayashi et al 2017;Starkweather & Perry 2017;White & Dixon 2015;Zvara 2017).…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…The PMP in this study is an evidence-based pain management (EBPM) programme that significantly decreased the pain intensity and side effects of the treatment (nausea and drowsiness). This is similar to the findings from other studies where EBPMs were implemented for post-operative pain management in different populations such as patients undergoing abdominal surgery (Joshi et al 2013), gastrointestinal surgery (Haghighi et al 2016), cardiac surgery (Rafiq et al 2014) and (Ard o et al 2018;Dinic et al 2018;Hayashi et al 2017;Starkweather & Perry 2017;White & Dixon 2015;Zvara 2017).…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Regardless of the type and extent of surgery, women reported slightly higher pain scores in the research of Gerbershagen HJ et al [29]. Haghighi M.J. et al, in their studies, showed that in patients undergoing general surgery, the mean pain intensity was significantly higher in men than in women [30]. Due to cultural differences between the studied groups, it would be advisable to conduct comparative studies.…”
Section: Discussionmentioning
confidence: 92%
“…When a significant change in worsening pain level is reported, reevaluate the patient for possible postoperative complications. A combined nurse service with clinician supervision seems to provide better outcomes in APP management [14,15,18,20,21,23,24,34,35]. It is proven that 24 h/day monitoring with a regular assessment/documentation guarantees a better pain treatment [14,20].…”
Section: Statementsmentioning
confidence: 99%
“…34 General Surgery Department, UCLA Davis University Hospital, Los Angeles, CA, USA. 35 General Surgery Department, Government Gousiua Hospital, Srinagar, India. 36 Emergency and Trauma Surgery Department, Milano University Hospital, Milan, Italy.…”
Section: Abbreviationsmentioning
confidence: 99%